Benefit and Risk of Prolonged Dual Antiplatelet Therapy After Percutaneous Coronary Intervention With Drug-Eluting Stents in Patients With Elevated Lipoprotein(a) Concentrations - Cui, Kongyong; Wang, Hao-Yu; Yin, Dong; Zhu, Chenggang; Song, Weihua; Wang, Hongjian; Jia, Lei; Zhang, Dong; Song, Chenxi; Feng, Lei; Dou, Kefei (Frontiers in Cardiovascular Medicine, 2021)
Background: Lipoprotein(a) is positively related to cardiovascular events in patients with coronary artery disease (CAD). Given that lipoprotein(a) has a prothrombotic effect, prolonged dual antiplatelet therapy (DAPT) might have a beneficial effect on reducing ischemic events in patients with elevated lipoprotein(a) levels after percutaneous coronary intervention (PCI). We performed this study to assess the efficacy and safety of prolonged DAPT (>1 year) in this population. Methods: We evaluated a total of 3,025 CAD patients with elevated lipoprotein(a) levels who were event-free at 1 year after PCI from the prospective Fuwai PCI Registry, of which 913 received DAPT ≤ 1 year and 2,112 received DAPT>1 year. The primary endpoint was major adverse cardiovascular and cerebrovascular event (MACCE), defined as a composite of all-cause death, myocardial infarction or stroke. Results: After a median follow-up of 2.4 years, patients who received DAPT>1 year were associated with lower risks of MACCE compared with DAPT ≤ 1 year (1.6 vs. 3.8%; hazard ratio [HR] 0.383, 95% confidence interval [CI] 0.238–0.616), which was primarily driven by the lower all-cause mortality (0.2 vs. 2.3%; HR 0.078, 95% CI 0.027–0.227). In addition, DAPT>1 year was also associated with lower risks of cardiac death, and definite/probable stent thrombosis than those who received DAPT ≤ 1 year (P < 0.05). Conversely, no difference was found between the two groups in terms of clinically relevant bleeding. Similar results were observed in multivariate Cox regression analysis and inverse probability of treatment weighting analysis. Conclusions: In patients with elevated lipoprotein(a) concentrations after PCI, prolonged DAPT (>1 year) reduced ischemic cardiovascular events, including MACCE, all-cause mortality, cardiac mortality, and definite/probable stent thrombosis, without increase in clinically relevant bleeding risk compared with ≤ 1-year DAPT. Lipoprotein(a) levels might be a new important consideration when deciding the duration of DAPT after PCI.